Hospital admission is associated with disability and late musculoskeletal pain in individuals with long COVID - Neto, Ricardo Bezerra Duarte; Reis, Luis Felipe Fonseca; Ferreira, Arthur de Sá; Alexandre, Dângelo José de Andrade; Almeida, Renato Santos de (Frontiers in Rehabilitation Sciences, 2023)
Background The acute clinical repercussions of SARS-CoV-2 infection have been widely studied. However, the possible late repercussions of long COVID have not yet been well defined in the literature. Objectives To identify the presence of pain and musculoskeletal disability in patients with Long COVID and also to identify predictive factors for pain intensity in this population. Methods In this cross-sectional and retrospective observational study individuals with Long COVID symptoms were included. It was collected musculoskeletal disability measures, data from patient-related outcome measures and variables from a COVID-19 outpatient service database. Associations and sub-group analyses were performed considering the variables pain, disability and hospitalization. Linear regression was performed to identify predictive factors for pain intensity in Long COVID patients. Results We evaluated 195 patients and most of them (57%) presented musculoskeletal pain in one area of the body. Pain sub-group presented worse disability indices and worse clinical course during hospitalization. Hospitalized patients presented worse disability indices comparing to non-hospitalized. Significant correlations were found between pain and days of non-invasive oxygen support (r = 0.21; p = 0.003); days in intensive care unit (r = 0.22; p = 0.002) and days in invasive mechanical ventilation (r = 0.35; p = 0.001). Hospitalized individuals showed a higher chance of presenting late musculoskeletal pain (OR = 1.42: 95%CI 1.09–2.04). Days in intensive care unit (β = 0,234: P = 0,001) and days in invasive mechanical ventilation (β = 0.764: P = 0.001) were predictors of pain intensity [F(2,192) = 18.559; R2 = 0.231; p = 0.001]. Conclusion Individuals with Long COVID presented musculoskeletal pain and disability. Hospitalized patients showed a greater chance of having musculoskeletal pain. Days in intensive care unit and days in invasive mechanical ventilation were predictors of late musculoskeletal pain intensity.